SEMICONDUCTOR LASER PROPERTY TO FORM INTERRUPTING RADIATION AT THE MOMENT OF SWITCHING ON AND SWITCHING OFF OF THE PUMPING ELECTRIC CURRENT - Lvovich, Churakov Valery; Valentinovich, Besogonov Valery (European Scientific Journal, ESJ, 2015)
Semiconductor laser property to form interrupting radiation at the moment of switching on and switching off of the pumping electric current, belonging to a field of semiconductor lasers physics is described. An amplitude modulation of radiation during the moments of switching of a pumping electric current has coherent character. The average period of fluctuations is determined by tens femtoseconds, the whole process duration is some tens picoseconds. The device can be used for the noncontact highspeed precision control of geometrical parameters of the items, various defects definition in optically transparent products. The result of the research is a basis for new directions in a laser tomography, the measuring technique, use of this property will essentially simplify laser and fiber-optical gyroscopes.